The Performance and Market Impact of Dual Trading: CME Rule 552 - Chang, Eric C.; Loche, Peter R. (Journal of Financial Intermediation, 1996)
This paper analyzes dual trading on futures contracts restricted by Chicago Mercantile Exchange Rule 552. Using floor trader data, several categories of traders are identified, and differences in strategies and profitability are examined. When unrestricted, dual traders execute most customer orders and few personal trades. The evidence supports the hypothesis that dual traders are superior brokers. However, there is no evidence of informational advantages in dual traders' personal trading. Dual traders are shown to provide liquidity with their personal trades. Finally, Rule 552 does not appear to have increased trading costs.Journal of Economic LiteratureClassification Numbers: G12, G13, D82.